Pemahaman Dinamika Kurang Percaya Diri Pada Remaja Berdasarkan Teori Kognitif - Auliyah Reski Sagita; Arianda Arianda; Qudratullah Qudratullah (Pusat Riset dan Inovasi Nasional, 2026)
Adolescence is a complex developmental stage, characterized by significant biological, social, and cognitive changes. One of the most common problems that emerge during this period is low self-esteem, which impacts mental health, social adjustment, academic achievement, and identity formation. This study aims to analyze the internal factors underlying low self-esteem in adolescents from a cognitive theory perspective. Using qualitative methods and a phenomenological approach, this study explores adolescents' subjective experiences related to thought processes, core beliefs, cognitive distortions, self-efficacy, cognitive patterns, and self-talk that play a role in shaping self-perception. The research findings indicate that negative core beliefs, automatic thoughts, and maladaptive cognitive distortions are the main internal mechanisms that lower self-esteem. Furthermore, low self-efficacy, impulsive or unbalanced reflective thinking styles, and negative self-talk reinforce self-doubt and trigger a cognitive cycle that is difficult to break.